« L’Académie des sciences et des beaux-arts » : le testament graphique de Sébastien Leclerc - Préaud, Maxime (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1983)
The engraver Sébastien Leclerc is very representative of the long reign of Louis xiv, with whom he is an almost exact contemporary. Admitted to the Royal Academy of Painting and Sculpture in 1672, he was also closely allied with the Royal Academy of Science (founded 1666) of which he was one of the preferred engravers. His entire life is divided between the sciences and arts, and he was not only a fine mathematician and physicist, but also collected instruments and experimental models. The print entitled The Academy of Sciences and Fine Arts, dedicated to the king in 1698, appears to be Leclerc’s graphic testament. In it he exposes not only his faith in scientific progress as opposed to the quackish barbarism personified by the chiromancer of the first plane, and his admiration for the reign of the prince who authorized scientific renewal, but he also shows with a discreet pride – in scattering throughout his plate very clear and specific allusions for connoisseurs of his own past or present works issuing from royal commissions or else arising from his own initiatives – that he is not the last person to have participated in this noble enterprise. While knowing that Death, hidden in an anamorphosis, awaits him, he hopes that his genius will survive and that he will have earned the right to the eternal gratitude of the scholarly community. Thus, by this meticulous and subtle work, an artist whose recognized first qualities are exactitude and positive realism is inscribed in the ‘metaphysical’ tradition usually associated with the painters of Vanities.